2023
DOI: 10.3390/medicina59071322
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Review of Clinical Factors Involved in Speech-Perspectives from a Prosthodontist Point of View

Abstract: Background and Objectives: Learning to speak properly requires a fully formed brain, good eyesight, and a functioning auditory system. Defective phonation is the outcome of a failure in the development of any of the systems or components involved in speech production. Dentures with strong phonetic skills can be fabricated with the help of a dentist who has a firm grasp of speech production and phonetic characteristics. Every dentist strives to perfect their craft by perfecting the balance between the technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…In labiodental or fricative sounds, the incisal edges of upper anterior teeth touch the lower lip line ('F' or 'v'). In linguaalveolar sounds, the tip of the tongue touches the palatal rugae ('s' or 'Ch' or 'j') also known as sibilant sounds [14]. In linguodental sounds, the tip of the tongue lies in between the upper and lower teeth ('this' or 'that') while pronouncing bilabial sounds, both the upper and lower lip will be in contact ('B' or 'M').…”
Section: Discussionmentioning
confidence: 99%
“…In labiodental or fricative sounds, the incisal edges of upper anterior teeth touch the lower lip line ('F' or 'v'). In linguaalveolar sounds, the tip of the tongue touches the palatal rugae ('s' or 'Ch' or 'j') also known as sibilant sounds [14]. In linguodental sounds, the tip of the tongue lies in between the upper and lower teeth ('this' or 'that') while pronouncing bilabial sounds, both the upper and lower lip will be in contact ('B' or 'M').…”
Section: Discussionmentioning
confidence: 99%
“…Clear articulation during speech expression necessitates adequate freeway space. Insufficient freeway space, whether due to malocclusion or pathophysiological variations in the TMJ complex, may affect patients' phonetic patterns, resulting in articulatory challenges during mandibular translation 31 , 32 . These variations, often imperceptible to the naked eye but detectable through optical landmark tracking and EGN, provide the models with sufficient data diversity to establish trends.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, VD plays a crucial role in speech, as it influences the position and movement of the tongue and lips, affecting phonetics and clarity of speech. Researchers found that difficulties pronouncing the sounds "b", "m", "p", "f", and "v" were most commonly related to an increased vertical dimension [31].…”
Section: Functional Considerationsmentioning
confidence: 99%